2020
DOI: 10.3390/ijms21103604
|View full text |Cite
|
Sign up to set email alerts
|

On-Target CRISPR/Cas9 Activity Can Cause Undesigned Large Deletion in Mouse Zygotes

Abstract: Genome engineering has been tremendously affected by the appearance of the clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated protein 9 (CRISPR/Cas9)-based approach. Initially discovered as an adaptive immune system for prokaryotes, the method has rapidly evolved over the last decade, overtaking multiple technical challenges and scientific tasks and becoming one of the most effective, reliable, and easy-to-use technologies for precise genomic manipulations. Despite its undoubt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 87 publications
(97 reference statements)
4
30
0
Order By: Relevance
“…Our new data are in line with recent publications where genome engineering resulted in unexpected larger rearrangements [ 15 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. Our findings support the observations of Boroviak and colleagues [ 16 ]; however, the high-frequency occurrence of inverted re-insertions using the dual sgRNA approach has not previously been described in this context.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our new data are in line with recent publications where genome engineering resulted in unexpected larger rearrangements [ 15 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. Our findings support the observations of Boroviak and colleagues [ 16 ]; however, the high-frequency occurrence of inverted re-insertions using the dual sgRNA approach has not previously been described in this context.…”
Section: Discussionsupporting
confidence: 91%
“…Our own research has observed frequent larger-than-expected deletions, potentially generated by the microhomology mediated end-joining (MMEJ) repair pathway [ 18 ]. Additionally, more recent findings report serial head-to-tail insertions of donor DNA templates [ 19 ]; error-prone repair pathways inserting unwanted deletions and insertions [ 20 ]; unintended ON-target chromosomal instabilities [ 21 ]; harmful chromosomal deletions [ 22 ]; and deleterious ON-target effects when aiming at homology directed repair (HDR) [ 23 ]. Hence, it is crucially important for precise model validation to know which outcomes CRISPR/Cas9 genome engineering can generate besides the actual aimed-for edit [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mice were maintained on a 12‐hour light/dark cycle with ad libitum food and water in a conventional animal facility 27 . All experiments were conducted at the Department of Experimental Animal Genetic Resources at the Institute of Cytology and Genetics, SB RAS (RFMEFI61914X0005 and FMEFI61914X0010).…”
Section: Methodsmentioning
confidence: 99%
“…Then, after purification, the DNA template was used for in vitro gRNA transcription using the HiScribe T7 High Yield RNA Synthesis Kit (NEB, E2040S, Ipswitch, MA, USA). The gRNA was purified on RNA Clean and Concentrator-25 columns (Zymo Research, R1017, Irvine, CA, USA) [ 53 ]. SpCas9 messenger RNA was purchased from a commercial manufacturer (GeneArt CRISPR Nuclease mRNA, Thermo Fisher Scientific, Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%